Italian fascist modernisation and colonial landscape in Albania 1925-1943 - Pandelejmoni, Enriketa (2021)
Environmental history and landscape transformations vis-à-vis agricultural modernization policies such as the reclaiming of land hardly features in studies on the Italian fascist annexation of Albania. This paper focuses on the main features of Italian economic and landscape efforts in Albania during the fascist years through a general overview of the Italian period with respect to economic and land reclamation works, and an exploration of Italys colonial policies in the modernization and regeneration of Albanian landscape. Its scope includes Italys interwar interventionist efforts in Albania in economy and land reclamation, but not the substantial literature on Italian contribution to the transformation of Albanian urban landscapes during the interwar period. The urban planning of Albania by Italian architects, engineers, and urbanists that developed from 1920 to 1939 has been dealt with extensively in scholarship regarding Albania.